Evaluation of Student Tahfidz Program Implementation Faculty of Social and Political Science Through the Countenance Evaluation Model Approach - Meli Fauziah; Mubarok Mubarok; Budi Budiman; Muhibudin Wijaya Laksana (Jurnal Perspektif, 2019)
All programs in the Faculty of Social and Political Sciences of UIN SGD Bandung are expected to produce outputs that have an impact on improving quality in all fields. Therefore, each program is always maintained its quality both in terms of planning, process and evaluation. The Countenance Evaluation Model is a model that raises broader insights in evaluating the implementation of a program, including the Student Tahfidz Institute. The purpose of this study was to determine the implementation of the Tahfidz Program Students of the Faculty of Social and Political Sciences UIN Bandung in terms of planning, process and evaluation of programs using quantitative descriptive method. The results showed that planning, process and program evaluation had a positive effect on the quality of the Tahfidz Program Implementation Faculty of Social and Political Sciences, UIN Bandung.